Development of Tennis Spin Serve Technique Observation Instrument: The Quality Tennis Learning in Higher Education - Aprilo, Ians; Arfanda, Poppy Elisano; Mappaompo, M. Adam; Asyhari, Hasbi; Hasanuddin, M. Imran; Syafir, Muhammad Isnawan (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study aims to develop and test the validity and reliability of an observation instrument for spin serve techniques in tennis. We designed this instrument to measure seven main aspects of the spin serve movement: coiling, toss, backswing, uncoiling, strike zone, follow-through, and fall-in. Using a quantitative approach and descriptive correlational design, this study involved 30 students who had taken advanced tennis lessons. The validity of the instrument was tested using the Pearson product-moment correlation, while the reliability was tested using the Cronbach's alpha coefficient. The results indicated that all aspects had correlation values above 0.3, and the reliability of the instrument was in the moderate category (α = 0.552). These findings indicate that the developed observation instrument is feasible to use in the context of spin serve tennis. We can conclude that novice athletes can effectively evaluate their performance using the observation instrument for spin serve techniques in tennis. All aspects have adequate validity, and the instrument as a whole shows moderate reliability. This instrument can be an initial reference in the process of training more objective and systematic spin-speak techniques, although it still needs improvement to increase reliability.